Rockets and feathers meet Joseph: Reinvestigating the oil-gasoline asymmetry on the international markets - Ladislav Kristoufek; Petra Lunackova (Charles University in Prague, Institute of Economic Studies (IES), 2015)
We reinvestigate the "rockets and feathers" effect between retail gasoline and crude oil prices in a new framework of fractional integration, long-term memory and borderline (non)stationarity. The most frequently used error-correction model is examined in detail and we find that the prices return to their equilibrium value much more slowly than would be typical for the error-correction model. Such dynamics is usually referred to as "the Joseph effect". The standard procedure is shown to be troublesome and we introduce two new tests to investigate possible asymmetry in the price adjustment to equilibrium under these complicated time series characteristics. On the dataset of seven national gasoline prices, we find no statistically significant asymmetry. The proposed methodology is not limited to the gasoline and crude oil case but it can be utilized for any asymmetric adjustment analysis.
Keywords: Q40; Q43; Q48; 330; rockets and feathers; asymmetry; gasoline; crude oil; cointegration